Initial growth of Syagrus romanzoffiana seedlings in biosolid-based substrate - de Souza, Antonio Maricélio Borges [UNESP]; Chioda, Larissa Benetasso [UNESP]; Ferreira, Kássia Barros [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; Campos, Thiago Souza [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2022)
Substrate composition is a major factor influencing seedling quality. This study aimed to evaluate the potential of biosolid as a substrate component in the initial growth of Syagrus romanzoffiana (Cham.) Glassman seedlings. The experimental design was completely randomized, with six treatments, five replicates and seven plants per plot. The treatments consisted of substrates resulting from the mixture of subsoil (SS) and biosolid (BIO) at different proportions: 100 % SS; 20 % BIO + 80 % SS; 40 % BIO + 60 % SS; 60 % BIO + 40 % SS; 80 % BIO + 20 % SS; 100 % BIO. The seedling quality and morphological characteristics were evaluated. There was an increase up to the proportion of 60 % of biosolid for shoot height, stem diameter, number of leaves, leaf area, total chlorophyll content, root length, shoot dry matter and Dickson’s quality index. For the root and total dry matter, increases occurred up to the proportion of 40 % of biosolid. Therefore, the use of biosolid in the proportions of 40 and 60 % in the substrate composition proved to be efficient, as they promoted a satisfactory initial growth (all seedlings presented shoot height between 30 and 40 cm and stem diameter of 5 mm) and quality of the evaluated seedlings.
Crescimento inicial de mudas de Syagrus romanzoffiana em substrato à base de biossólido
Keywords: Arecaceae; jerivá; organic compost; sewage sludge